Ethnobotanical Survey and Sociocultural Uses of Two Plant Species of the Genus Alstonia (Apocynaceae) in the Kungu Territory (South Ubangi) in the Democratic Republic of the Congo - J.B.Z. Bosanza; K.N. Ngbolua; D.B. Manzongo; C.A. Masengo; M. Monizi (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The aim of the present study is to provide actors interested in herbal medicine with endogenous knowledge on the medicinal and traditional uses of Alstonia boonei and A. congensis in the Kungu territory. The survey revealed that both are widely used either alone or in combination with other species and contribute to the treatment of many diseases. Endogenous knowledge of these two species and their medicinal-traditional uses reveal that 23 kinds of diseases are treated, of which snakebite the only disease is commonly treated by the three sociocultural groups targeted in this study, namely Bomboma, Ngbandi, and Ngombe. Of the different plant parts used in the preparation of therapeutic recipes, bark dominates with 58.8%, followed respectively by sap (22.4%), leaves (12.9%), and roots (5.9%). Finally, as forests are increasingly threatened, it would be imperative to preserve these two medicinal species by developing, for example, their cultivation and thus guarantee a sustainable and regular supply of organs used as raw materials in the preparation of medicinal recipes.